2021
DOI: 10.1158/1078-0432.ccr-20-2385
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Reovirus (pelareorep) Induces Autophagy in KRAS-mutated Colorectal Cancer

Abstract: Purpose: To explore the effects of pelareorep on autophagy in multiple models of colorectal cancer, including patient-derived peripheral blood mononuclear cells (PBMCs). Experimental Design: HCT116 [KRAS mutant (mut)] and Hke3 [KRAS wild-type (WT)] cells were treated with pelareorep (multiplicity of infection, 5) and harvested at 6 and 9 hours. LC3 A/B expression was determined by immunofluorescence and flow cytometry; five a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…AMPK induced misfolded PPARδ-S50 phosphorylation leading to inhibition of p62-mediated misfolded PPARδ autophagic degradation. Other reports suggest that KRAS could regulate autophagy (47,48), and SW480 and HCT116 are KRAS mutant colonic cancer cells, whereas the increased PPARδ protein levels were similar to KRAS wild type (CW-2, HT-29) colonic cancer cells (SFigure. 2).…”
Section: Discussionmentioning
confidence: 93%
“…AMPK induced misfolded PPARδ-S50 phosphorylation leading to inhibition of p62-mediated misfolded PPARδ autophagic degradation. Other reports suggest that KRAS could regulate autophagy (47,48), and SW480 and HCT116 are KRAS mutant colonic cancer cells, whereas the increased PPARδ protein levels were similar to KRAS wild type (CW-2, HT-29) colonic cancer cells (SFigure. 2).…”
Section: Discussionmentioning
confidence: 93%
“…However, an oncogenic function for autophagy has generally been aligned with specific oncogenic status of the cancer cells and/or genetic mutations [ 49 ]. In this regard, studies have suggested that cancer cells harboring K-ras mutation are autophagy addicted [ 49 , 50 ]. While our findings support the role of the autophagy in promoting the resistance to chemotherapy, they also suggest that autophagy is an essential property of colon cancer cells irrespective of the cancer stage or genetic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirms that reovirus (commercially known as pelareorep) has a profound effect on gene expression in patients with KRAS mutated CRC. We have previously shown using the same transcriptome data set that immune related genes 8 , 46 and autophagy-related genes 47 are significantly upregulated upon reovirus treatment. Herein, we have further analyzed and reported the genes that are altered in seven important cellular pathways, including the RAS signaling pathway.…”
Section: Discussionmentioning
confidence: 98%